Establishing the diagnosis neurofibromatosis type 1: A rare case - Dyatiara Devy; D. Damayanti (PAGEPress Publications, 2019)
Neurofibromatosis type 1 (NF1) or Von Recklinghausen's disease is a dominantly inherited genetic, multisystem disorder. Individuals with neurofibromatosis type 1 are prone to develop benign and malignant tumors of the CNS and peripheral nervous system, in addition to malignant diseases affecting other parts of the body. About 50% of individuals with neurofibromatosis type 1 have no family history of the disease and the disease is due to de novo (spontaneous) mutations. Early diagnosis is challenging because of its extremely variable characteristics. Some individuals may be mildly affected showing minimal signs, whereas others are severely afflicted. Individuals with NF-1 are best cared for within a multidisciplinary clinic, which has access to a wide range of subspecialists. The dermatologist has a role not only in the diagnosis of NF1 and differentiating it from other similar disorders, but also in the recognition of rare associated skin manifestations.